2021
DOI: 10.3390/ijerph18073405
|View full text |Cite
|
Sign up to set email alerts
|

Green Remanufacturer’s Mixed Collection Channel Strategy Considering Enterprise’s Environmental Responsibility and the Fairness Concern in Reverse Green Supply Chain

Abstract: In reverse green supply chain, the mixed collection channel strategy of green remanufacturer is analyzed by building a dynamic game model in which we consider that the green remanufacturer undertakes the environmental responsibility and the green collector shows strong fairness concern for the profit. We analyze the impact of the environmental responsibility level of the green remanufacturer, the preference coefficient of the green remanufacturer, the fairness concern coefficient of the green collector, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Enterprise performance is measured using the return on assets and sales growth rate through factor and cluster analysis [5]. For example, some studies have found that adopting a deviated enterprise strategy will positively impact enterprise performance [6]. Moreover, some studies believe that the reason for the uncertainty of enterprise performance is that the enterprise mainly adopts the industry conventional strategy when its strategy is chosen [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Enterprise performance is measured using the return on assets and sales growth rate through factor and cluster analysis [5]. For example, some studies have found that adopting a deviated enterprise strategy will positively impact enterprise performance [6]. Moreover, some studies believe that the reason for the uncertainty of enterprise performance is that the enterprise mainly adopts the industry conventional strategy when its strategy is chosen [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wu et al [3] developed closed-loop supply chain models for joint environmental responsibility investment, recycling and pricing decisions, and found recycling strategy of third-party-led collection is disadvantageous. Yuan et al [43] investigated green remanufacturer's mixed collection channel strategy considering enterprise's environmental responsibility and fairness concern, and showed the impact of environmental responsibility on optimal decision.…”
Section: Supply Chain Operations With Corporate Environmental Responsibilitymentioning
confidence: 99%
“…Yuan et al [8] examined the effect of green activities. e purpose of their study is to analyze the effects of environmental programs on each of the goals (economic and environmental).…”
Section: Introductionmentioning
confidence: 99%